Effect of home‐based exercise with or without a Mediterranean‐style diet on adiposity markers in postmenopausal women: A randomized‐control trial - Abbigail Tan; Gareth Dunseath; Rebecca L. Thomas; Sarah L. Prior; Richard M. Bracken; Rachel Churm (Physiological Reports)
Abstract Advancing age and estrogen deficiency increases susceptibility of post‐menopausal women (PMW) to abdominal obesity and manifestation of cardiometabolic disease. There is limited evidence on the effect of lifestyle interventions on adiposity markers within at‐risk PMW. Therefore, this study aims to evaluates an 8‐weeks of home‐based, equipment‐free, interval training (HEFIT) with or without Mediterranean‐style diet (MD) on adiposity markers in physically inactive, postmenopausal women with overweight/obesity. Thirty PMW (56.7 ± 3.9 years, BMI: 30.5 ± 5.2 kg/m2) were randomly assigned to three groups: (i) Ex; HEFIT thrice weekly/week, (ii) EX + MD, or (iii) CTL; control. Visceral Adiposity Index (VAI), body weight, BMI, waist and hip circumference (WC; HC), visceral adipose tissue (VAT), total body fat percentage, leptin, and adiponectin were determined pre‐ and post‐8‐week intervention. There was no significant between group effect on VAI. Compared to CTL, a significant between group reduction was seen in weight, BMI, and WC in both EX and EX+D (p < 0.05). Leptin and adiponectin remained unchanged in all groups (p > 0.05). Adherence rates were 85% and 96% for EX and EX+MD, respectively, and 80% of EX+D of participants had optimal adherence to diet. Concluding HEFIT with or without dietary changes could improve adiposity in overweight/obese postmenopausal women.